Gaming Complex with Esports Stadium and Training Facility - Rey, Reinhardt P.; Madrid, Dolores Cecelia T. (Quezon City College of Architecture, University of the Philippines Diliman, 2020)
This thesis presents a gaming complex with a training facility for the development of Filipino esports and its athletes. The design, located in Vertis North, Quezon City, takes into account the site's accessibility as a business district to maximize the booming esports industry, specifically the world class esports potential in the Philippines. To do this, the complex translates the concepts to clustering and community spaces to achieve an environment that prioritizes work-play balance. The complex includes the training rooms for both new teams and more established teams, game development studios for both big and small companies, and a mall catered to gamers for the general gaming population, creating an environment that is collaborative and competitive, and creates a strong sense of community. The highlight of the complex is the country's first stadium dedicated to Esports, acting as both a community space and symbol for games, as well as a crucible for professional Esports athletes to further hone their skills against players of their caliber, at the same time strengthening bounds between the players and fans. Backed by successful feasibility studies, this thesis aims to be a possible vision into a future where the Philippines not only legitimizes, but fully supports its global-caliber esports athletes.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Sports facilities